EVALUASI EFEKTIVITAS PENGAMANAN ASET DAERAH BERUPA KENDARAAN DINAS PADA KANTOR BPKAD KABUPATEN SIKKA - Ignasius Damianus Nong Kelvin; Imanuel Wellem; Viktor Eko Transilvanus (Universitas Nusa Nipa Maumere, 2026)
This research aimed to evaluate the effectiveness of safeguarding regional assets in the form of official vehicles at the Regional Financial and Asset Management Agency (BPKAD) of Sikka Regency. Asset security is an essential component in the management of regional government assets to ensure orderly governance, physical security, and legal certainty regarding asset ownership. This study employs a qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted descriptively based on indicators of administrative security, physical security, legal security, as well as supervision and control. The results show that the security of official vehicle assets has been implemented through administrative recording, safekeeping of ownership documents, and monitoring of vehicle usage. However, its effectiveness is not yet optimal, as there are still official vehicles that have not been returned after the end of officials’ terms of office, along with weak enforcement of sanctions and limited periodic monitoring. Factors affecting the effectiveness of asset security include budget constraints, low user awareness, and suboptimal implementation of internal control systems. This study recommends strengthening supervision, conducting re-inventory of official vehicles, enforcing stricter sanctions, and improving coordination among regional government agencies to achieve more orderly, transparent, and accountable asset management